EMPOWERING FUTURE TEACHERS: STUDENTS' EXPERIENCE CREATING EFL MEDIA IN KAMPUS MENGAJAR PROGRAM - Chessy Artika; Hafizhatu Nadia; Miftah Al Farhan; Noor Aida Aflahah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study explores how a Teaching Media course shapes prospective EFL teachers’ abilities to design and implement effective instructional media, addressing the urgent need for educators who can integrate engaging learning tools in diverse classroom settings. Unlike previous research that focuses solely on media use in higher education, this study offers a novel perspective by examining how students transfer classroom learning to real teaching contexts through the Kampus Mengajar program. Using a qualitative narrative approach, data were collected through interviews with English education students who completed the Teaching Media course and participated in Kampus Mengajar. The findings show that the course significantly enhanced students’ pedagogical skills, creativity, and confidence in selecting and applying teaching media. Moreover, their classroom experiences during Kampus Mengajar confirmed the practical relevance of the course, demonstrating its contribution to preparing resourceful and adaptive future EFL teachers. This study underscores the importance of integrating media-focused training in teacher education programs.